2013
DOI: 10.1302/0301-620x.95b8.31574
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of a ceramic-on-metal bearing in total hip arthroplasty

Abstract: We prospectively assessed the efficacy of a ceramic-on-metal (CoM) hip bearing with uncemented acetabular and femoral components in which cobalt-chrome acetabular liners and alumina ceramic heads were used. The cohort comprised 94 total hip replacements (THRs) in 83 patients (38 women and 45 men) with a mean age of 58 years (42 to 70). Minimum follow-up was two years. All patients had pre- and post-operative assessment using the Western Ontario and McMaster Universities osteoarthritis index (WOMAC), Oxford hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
1
4
0
2
Order By: Relevance
“…However, one study suggested that any increase in metal ions was comparable between CoM and MoM groups at 1 year, perhaps explained by a bedding in phase [8] and no conclusion on clinical application could be made. There are reports of uncertainty in the performance of CoM bearings with regard to metal ion levels [9,10], which our study supports, with increasing Cr levels at 5 years despite a promising initial response up to 3 years. We are not aware of any other study following up a CoM bearing at longer term.…”
Section: Discussionsupporting
confidence: 78%
“…However, one study suggested that any increase in metal ions was comparable between CoM and MoM groups at 1 year, perhaps explained by a bedding in phase [8] and no conclusion on clinical application could be made. There are reports of uncertainty in the performance of CoM bearings with regard to metal ion levels [9,10], which our study supports, with increasing Cr levels at 5 years despite a promising initial response up to 3 years. We are not aware of any other study following up a CoM bearing at longer term.…”
Section: Discussionsupporting
confidence: 78%
“…Algorithms designed to help surgeons navigate clinical encounters with painful MoM hips may or may not be applicable to CoM and MoC hips 4 , 5 . Elevated serum metal ion levels after CoM THA has previously been reported and is associated with an increase in chromosomal breaks, aneuploidy in peripheral lymphocytes, and systemic symptoms including vision changes and hearing loss 12 , 13 , 16 , 18 .…”
Section: Discussionmentioning
confidence: 77%
“…Initial enthusiasm for CoM and MoC hips originated from industry-sponsored hip simulator analyses 9 , 10 , 11 and a limited number of in vivo clinical trials with short-term follow-up 11 , 12 , 13 . Despite previous reports of CoM and MoC bearing surfaces possessing good functional outcomes at short-term follow up, elevations in cobalt and chromium levels were observed that often paralleled levels seen in patients with MoM hips 11 , 12 , 13 . The significance of elevated metal ion levels was underappreciated at the time, and it is estimated that the CoM bearing surface combination alone was used in >10,000 THAs [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Для ендопротезування колінних та кульшових суглобів при термінальних стадіях гонартрозу й коксартрозу зазвичай використовуються штучні зчленування, що містять, Co, Cr, Mo, Ti, V та інші метали [9]. H. A. Kazi et al [10] встановили, що після двох років існування в організмі хворих таких ендопротезів тільки рівень V у крові не змінюється, тоді як концентрації інших металів значно зростають. J. Steinberg et al [11] було показано, що несприятливий перебіг ГКА після ендопротезування суглобів штучними зчленуваннями, що містять кобальто-хромовый сплав, супроводжується збільшенням у крові рівнів і Со, і Cr.…”
Section: Conclusion Gonocoxarthrosis Is Accompanied By Microelementunclassified